Are there bubbles in the Sterling-dollar Exchange Rate? New evidence from Sequential ADF Tests - Timo Bettendorf; Wenjuan Chen (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2012)
There has been mixed evidence regarding the existence of rational bubbles in the foreign exchange markets. Standard unit root and cointegration tests are criticized for their low power to detect rational bubbles that periodically collapse. This paper introduces recently developed sequential unit root tests into the analysis of exchange rates bubbles. Our results show that explosiveness in the nominal Sterling-dollar exchange rates is fully explained by the relative prices of traded goods.
Keywords: C1; F3; 330; exchange rates; rational bubbles; sequential unit root test